Massive unilateral fetal axillary lymphangioma: A case report - Dana M. Hutchison; Brian A. Crosland; Larry Wang; Michael P. Nageotte (Elsevier, 2021)
We report a substantial axillary lymphangioma in a fetus delivered at 38 weeks of gestation. Detailed fetal survey at 20 weeks revealed a 5.45 × 3.72 cm nonvascular cystic axillary structure without other malformations; amniocentesis was negative. Serial surveillance was performed throughout the pregnancy. A male infant weighing 3000 g with a 16 × 12 × 9 cm septated cystic mass arising from the left axilla was delivered via cesarean section. The newborn period was complicated by cellulitis overlying the mass and interval cystic hemorrhage requiring sclerotherapy and subsequent excision. Nonnuchal lymphangiomas may be etiologically distinct entities. The prognostic factors include anatomic location, presence of septa, and association with other congenital abnormalities. A thorough evaluation, multidisciplinary approach, and close surveillance should be undertaken to optimize neonatal outcomes.